ダイ9ジ ナンキョク チイキ カンソクタイ エットウタイ ホウコク 1968 1969 - 村山, 雅美; ムラヤマ, マサヨシ; MURAYAMA, Masayoshi (国立極地研究所, 1969)
P(論文) The National Antarctic Committee of the Science Council of Japan has decided to resume scientific research in the Antarctic by reopening Syowa. This base will serve as a permanent station for carrying out various kinds of observations and surveys of the East Antarctic Continent. The inland survey is for the purpose of studying continental ice, crustal structure, and geomagnetism following the geomagnetic meridian. During the period of February 11, 1968 to February 20, 1969 Syowa was manned by the 9th wintering party. The party consisted of the writer, who succeeded Dr. T. TORII as leader, plus 28 men including one correspondent of the press On account of the location of Syowa lying directly below the auroral zone, studies in the field of upper atmosphere physics have been conducted in continuation of last wintering party. We are limited in the scale of the station facility because of the transport capacity of the relief ship FUJI, but we were able to commence the study of cloud physics and medical science. The largest and highest ice continent in Antarctic lies to the south of Syowa. The distance between it and the South Pole is approximately 2,300 kilometers as the crow fhes While U. S. A. and U. S. S. R. have initiated an ambitious survey of the East Antarctic, the large portion of the continent remains unexplored A significant but hazardous scientific project remaining is the traverse between Syowa and the South Pole The Japanese expedition commenced the execution of this traverse. KD60, specially constructed snowmobile, was made available for the Pole trip Its special features include ability to withstand temperatures as low as minus 60 degrees Centigrade in the traverse over the ice plateau of the altitude of higher than 4,000 meters for a distance of 6,000 kilometers. The vehicle is equipped with a seismograph, an ice radar, a natural radio waves receiver, a gyrosyncompass for navigation, and radio transmitters and the like. It contains four berths plus kitchen and is capable of continuous ...